Do Carandiru ao parque da Juventude : reconstrução da paisagem urbana - Bianchini, Douglas Alves (2018)
The present research intends to analyze the urban landscape as a mutable phenomenon that adapts the needs of a society, considering this process in a historical perspective. The urban landscape is the physical and social space where our existential relations are given. This research deals with the territory of the Carandiru Complex and its surroundings, which runs from the central region of Santana to the banks of the Tietê River, located in the northern part of the city of São Paulo, belonging to the regional prefecture of Santana / Tucuruvi. This territory, rich in history, underwent a process of transformation, the result of an urban project that aimed to transform a part of the old State Penitentiary complex that was deactivated and demolished giving place to leisure and culture, the Youth Park and the Library of São Paulo, thus transforming the urban landscape of this region and its uses. The general objective of this research is to understand how the transformation of the State Penitentiary Complex, the scene of innumerable major episodes such as the massacre of 111 prisoners in 1992, in Parque da Juventude, interfered in the urban landscape of this region and how this redefined the related collective memory to the territory, and what role it plays within the city. We assume that the urban landscape of Carandiru neighborhood was modified, and that this process generated by the implantation of a park with several urban equipments, like poliesportivas courts, technical schools and library, interfered in the way of perception of this space by the society, to appropriate a new way of this area and of its requalifiedurbanlandscape.